Anti-corruption and financial transparency legislations - Igbudu, S. O. (Kaduna, Nigeria : Joyce Publishers, 2008)
The book contains information on the provisions of the Corrupt Practices Act 2000 and the Economic and Financial Crime Commission Act, 2004. It creates awareness and understanding of the provision of the various legislations.
oif 09/07/14
Loan
Keywords: Corruption -- Nigeria; Commercial crimes -- Nigeria